Influence of inorganic fertilization on production parameters of two varieties of sweet potato - Cobeña , Gloria; Zambrano, Eddie; Ruilova , Favio; Ortiz, Xavier; Hwan , Chang (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
In order to determine the effect of inorganic fertilization treatments on the productive behavior of the sweetpotato varieties "INIAP-Toquecita" and "INIAP-Buena Vista", this research was carried out during the dry season (June–December 2022) at the Estación Experimental Portoviejo del Instituto Nacional de Investigaciones Agropecuarias-INIAP, in the Colón parish, canton Portoviejo, province of Manabí, Ecuador. A randomized complete block design was used with three replications, and the following variables were analyzed: percent yield, total number of guides per plant, length of guides, mass of 100 guides, foliage yield, and number and yield of commercial roots. The inorganic fertilization treatments under study were: 1. N+P2O5+K2O+S+Mg+B; 2. N+P2O5+K2O+S+Mg+B+Zn+Mn+Fe; 3. 50 % more N+P2O5+K2O+S+Mg+B with respect to treatment 1; 4. N+P2O5+K2O; and 5. no fertilizers (control). It was evidenced that the inorganic fertilization treatments implemented on the variety "INIAP-Buena Vista" outperformed the results of the control, while treatments 1 and 2 of inorganic fertilization implemented on the variety "INIAP-Toquecita" outperformed the control. It was observed that the most favorable scenario for maximizing the yield of commercial tuberous roots in the variety "INIAP-Buena Vista" was treatment 3, which had 50 % more macro and micronutrients per hectare added to the soil with respect to treatment 1. The varieties evaluated did not show nutritional deficiencies during the production cycle (120 days).